Effects of 4-nonylphenol on the steroidogenesis of human adrenocarcinoma cell line (NCI-H295R). Issue 3 (23rd February 2017) - Bistakova, Jana; Forgacs, Zsolt; Bartos, Zsuzsa; Szivosne, Maria Racz; Jambor, Tomas; Knazicka, Zuzana; Tvrda, Eva; Libova, Lubica; Goc, Zofia; Massanyi, Peter; Lukac, Norbert
ABSTRACT: In this study, the human H295R adrenocarcinoma cell line was exposed to different concentrations (0.04, 0.2, 1.0, 2.5 or 5 µg/mL) of nonylphenol (NP) to investigate its impact on the inhibition or induction of the steroid hormones production during 48 h of in vitro culture. The hormone production was measured using ELISA kits. Results of this in vitro study suggest various effect of nonylphenol in relatively low concentrations on the selected steroid hormones production by the human H295R adrenocarcinoma cell line. The inhibiting impact on progesterone and androstenedione production was observed. The amount of progesterone was significantly decreased at 1.0, 2.5 and 5 µg/mL NP. Equally, the androstenedione production significantly decreased at 5 µg/mL NP. On the other hand, the amount of testosterone and 17β-estradiol was induced after nonylphenol exposition. The significant increase of testosterone level was found out at treatment with 5 µg/mL NP. 17β-estradiol production significantly increased at the doses of 2.5 and 5 µg/mL NP.